Impact of N-methyl-2-pyrrolidone in monoethanolamine solution to the CO2 absorption in packed column: Analysis via mathematical modeling Kesan N-metil-2-pirolidon dalam larutan monoetanolamina pada penyerapan CO2 dalam kolum pek: Analisis melalui pemodelan matematik - Tan, L.S. (Penerbit Universiti Kebangsaan Malaysia, 2020)
This work investigates the reason behind the change of CO2 absorption behaviour exhibited by monoethanolamine (MEA) solution via mathematical modeling analysis when physical absorbent, i.e. n-methyl-2-pyrrolidone (NMP), was added into the solution. The mathematical modeling included the heat model using time resolved numerical method. Based on the results, it was found that lower CO2 removal performance with the addition of NMP into MEA solution at pressure of 0.1 MPa was mainly due to the lower temperature rise along the column, which resulted in lower reaction rate. However, at 3 and 5 MPa pressure conditions, the high physical absorption capability contributed by the presence of NMP in MEA hybrid solution enhanced the CO2 absorption performance of MEA hybrid solution significantly. As such, temperature rise of solution was identified as the dominating factor affecting the performance of the hybrid solvent. The reaction rate of MEA was not affected by the addition of physical solvent. This finding shed crucial insight on the behaviour MEA-NMP hybrid solution which can be applied during scale-up of the process. Â© 2020 Penerbit Universiti Kebangsaan Malaysia. All rights reserved.